Submerged oceanic shoals of north Western Australia are a major reservoir of marine biodiversity - Moore, Cordelia; Cappo, M.; Radford, B.; Heyward, A. (Springer Verlag, 2017)
This paper provides a first assessment of fish communities associated with the submerged oceanic banks and shoals in north-west Australia. Until recently, little was known about these deeper and more inaccessible reefs. The mesophotic coral-reef habitats (20–80 m) were a major reservoir of marine biodiversity, with unique and exceptionally high fish diversity and abundance. Species richness in the study region was 1.4 times, and abundance almost twice, that recorded for similar mesophotic habitats on the Great Barrier Reef in north-east Australia. A review of the published literature revealed that Australia’s NW oceanic shoals support the highest fish species richness reported for mesophotic reefs to date. We made regional comparisons of fish community structure (species composition, richness and abundance) and assessed the influence of depth, substrate and location. The presence of consolidated calcareous reef, depth and aspect (a surrogate for exposure) had the greatest influence on species richness. In contrast, aspect and the presence of benthic biota had the greatest influence on fish abundance. Sites most exposed to the prevailing currents (facing north-east) had lowest fish abundance, while highest abundances were recorded on moderately exposed sites (along the north-west and southeast edges). The most abundant species were small (Pomacentrus coelestis) and large (Naso hexacanthus) planktivorous fish. Currently, 29.3% of NE Australia mesophotic reefs are within no-take management zones of the Great Barrier Reef. In contrast, just 1.3% of the NW oceanic shoals are designated as no-take areas. The location and extent of mesophotic reefs remain poorly quantified globally. Because these habitats support significant biodiversity and have the potential to act as important refugia, understanding their extent is critical to maintaining coral-reef biodiversity and resilience and supporting sustainable management.